Karl Marx: Greatness and Illusion. By Gareth Stedman Jones. London: Penguin Books, 2017, pp. 768. Paper Back. ISBN 978-0- 141-02480-6. - Zamri, Zahid (Intellectual Discourse, 2018)
As early as page 2 in Karl Marx: Greatness and Illusion, Stedman Jones boldly highlights that “(t)he invention of what came to be called as ‘Marxism’ was initially in large part the creation of Engels in his books and pamphlets, beginning with Anti-Dühring in 1878”. He further adds, as keepers of Marx’s works, the leaders of the German Social Democratic Party, including August Bebel, Karl Kautsky, Eduard Bernstein, and Franz Mehring, were also responsible for further mystifications of Marx by hiding the embarrassing gaps between the image and reality of Marx and his theory. This was ostensibly done in order to protect the party – which had Marx as its founding theorist – from being attacked and discredited by the ruling power which was the imperial government of Wilhelmine Germany (p. 2-3). Jones subsequently states, “From the beginning, what came to be called as ‘Marxism’ had been built upon an unambiguously selective view of what was to count as theory, not only in relation to would-be heretics, but also in relation to Marx himself” (p. 4). Afterwards he reveals a content from Bebel’s letter to Kautsky: “By the way, I want to tell you – but please keep absolutely quiet about it – that some of the letters (Marx’s) were not published, above all, because they were too strong for us” (p. 4). These punchlines are more than enough to shake the general understanding of Marx and “Marxism” to acclaiming Marxists and critical theorists alike.